Kajian Eksperimental Pengering Kopi Hybrid dengan Sistem Kontrol Temperatur Berbasis Mikrokontroler - Sanubary, Iklas; Santoso, Pande Putu Agus; Suhendra, Suhendra (Politeknik Negeri Padang, 2024)
This study aims to determine the performance of a hybrid coffee dryer with a microcontroller-based temperature control system. The heating sources used are sunlight and electric heater. The type of coffee used is liberica. The research method used is experimental, with the independent variable being time and the dependent variables being temperature and mass. Data collection was carried out for 4 consecutive days, starting at 09.00 WIB to 15.00 WIB with a data collection interval of every 20 minutes. The data measured were the temperature inside and outside the drying room and the mass of coffee before and after the drying process. Data analysis was done based on graphs, determining the drying rate and testing the coffee moisture content. The results showed that the average temperature difference measured inside and outside the drying room for 4 consecutive days was 17.21 oC. The total reduction in coffee mass in the dryer for 4 consecutive days was 572 grams with an average drying rate of 23.83 grams/hour. The results of coffee moisture content testing showed that the hybrid coffee dryer reduced coffee moisture content from 56.01% to 8.79%.